Promotion of vascular integrity in sepsis through modulation of bioactive adrenomedullin and dipeptidyl peptidase 3. (30th December 2020) - van Lier, D.; Kox, M.; Pickkers, P.
Abstract: Sepsis represents one of the major medical challenges of the 21st century. Despite substantial improvements in the knowledge on pathophysiological mechanisms, this has so far not translated into novel adjuvant treatment strategies for sepsis. In sepsis, both vascular tone and vascular integrity are compromised, and contribute to the development of shock, which is strongly related to the development of organ dysfunction and mortality. In this review, we focus on dipeptidyl peptidase 3 (DPP3) and adrenomedullin (ADM), two molecules that act on the vasculature and are involved in the pathophysiology of sepsis and septic shock. DPP3 is an ubiquitous cytosolic enzyme involved in the degradation of several important signalling molecules essential for regulation of vascular tone, including angiotensin II. ADM is a key hormone involved in the regulation of vascular tone and endothelial barrier function. Previous studies have shown that circulating concentrations of both DPP3 and ADM are independently associated with the development of organ failure and adverse outcome in sepsis. We now discuss new evidence illustrating that these molecules indeed represent two distinct pathways involved in the development of septic shock. Recently, both ADM‐enhancing therapies aimed at improving endothelial barrier function and vascular tone and DPP3‐blocking therapies aimed at restoring systemic angiotensin responses have been shown to improve outcome in various preclinical sepsis models. Given the current lack of effective adjuvant therapies in sepsis, additional research on the therapeutic application of these peptides in humans is highly warranted. Abstract :